Implementing IPv6 for Windows NT - Draves, Rich; Mankin, Allison; Zill, Brian (Proceedings of the 2nd USENIX Windows NT Symposium, 1998)
We have created a publicly-available implementation of IPv6 for Windows NT> Because we have made our source code available, we hope that our implementation can serve as a base for networking research and supply sample code for other implementations. In this paper we describe our solutions for several problems that any network protocol implementation for Windows NT will encounter. Based on our experience, we also comment on the utility of access to the source code for the Windows NT product.